Alnustone inhibits the growth of hepatocellular carcinoma via ROS‐ mediated PI3K/Akt/mTOR/p70S6K axis. (30th November 2021) - Wang, Linlin; Cheng, Li; Ma, Li; Ahmad Farooqi, Ammad; Qiao, Gan; Zhang, Yuxi; Ye, Hanlin; Liu, Minghua; Huang, Jianlin; Yang, Xiaohui; Lin, Xiukun; Cao, Shousong
Abstract: Alnustone, a diarylheptane compound, exhibits potent growth inhibition against hepatocellular carcinoma (HCC) BEL‐7402 cells. However, the underlying mechanisms associated with its anticancer activity remain unknown. In the present study, we evaluated the anticancer effect of alnustone against several human cancers focused on HCC and the possible associated mechanisms. The results showed that alnustone significantly inhibited the growth of several cancer cells by CCK‐8 assay. Alnustone markedly induced apoptosis and decreased mitochondrial membrane potential in BEL‐7402 and HepG2 cells. Alnustone inhibited the expression of proteins related to apoptosis and PI3K/Akt/mTOR/p70S6K pathways and generated ROS production in BEL‐7402 and HepG2 cells. Moreover, N‐acetyl‐L‐cysteine (NAC, a ROS inhibitor) could significantly reverse the effects of alnustone on the growth inhibition of BEL‐7402 and HepG2 cells and the expression of proteins related to apoptosis and PI3K/Akt/mTOR signaling pathway in HepG2 cells. Furthermore, alnustone significantly inhibited tumor growth of HepG2 xenografts, obviously induced apoptosis in the tumor tissues and improved the pathological condition of liver tissues of mice in vivo. The study provides evidence that alnustone is effective against HCC via ROS‐mediated PI3K/Akt/mTOR/p70S6K pathway and the compound has the potential to be developed as a novel anticancer agent for the treatment of HCC clinically.